Analisis komparatif kemiskinan di Sumatera Periode 2010-2020 - Aldian, Aldian; Tan, Syamsurijal; Syafri, Muhammad (Jurnal Paradigma Ekonomika, 2024)
The purpose of this study is to analyze the development of education level, unemployment rate, income per capita, poverty level, poverty depth index and poverty severity index between provinces in Sumatra Island during the period 2010-2020 and analyze the effect of education level, unemployment rate and per capita income on the level poverty, poverty depth index and poverty severity index among provinces on the island of Sumatra during the period 2010-2020. This type of research is quantitative research and the analytical tool used is panel data regression. Based on the results of the study, it can be concluded that during the period 2010 to 2020, the variables that can affect the poverty level of the provinces in Sumatra are the level of education, the unemployment rate and per capita income. Furthermore, the variables that can affect the poverty depth index of the provinces in Sumatra are education level and unemployment rate. While the variables that can affect the poverty severity index of the provinces in Sumatra are the unemployment rate variables.